Household Business Development Strategy in Cemara Beach Banyuwangi (Case Study of Housewives' Business KUB Pantai Rejo) - Elok Rosyidah; Sahru Romadloni (Journal of Aquaculture Science, 2021)
Mangroves are one of the typical coastal ecosystems that have important functions and roles for the continuation of coastal areas. In the coastal environment, mangrove forests are important natural resources that have three main functions, namely physical functions, biological functions and economic functions. The economic function generated by the mangrove forest is utilized by the Joint Business Group (KUB) of Pantai Rejo, especially the Women's Group. One of them is making dumpling crackers made from mangrove leaves and making syrup made from mangrove fruit seeds. The problems faced by KUB Pantai Rejo are product/business licensing, capital, marketing. The purpose of this study is to provide a strategy for the development of the banyuwangi pine beach household industry. The type of research used in this research is descriptive qualitative using a literature study and field study approach. Providing driving factors as a business development effort, namely the involvement of the government and related parties, easy access to capital, assistance to conduct business legality (PIRT), training and development with marketing strategies and online promotions. Keywords: Business Development Strategy, Cemara Beach, and Mangroves.